2013
DOI: 10.1093/hmg/ddt165
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 signaling increases utrophin A expression in skeletal muscle via the RNA-binding protein KSRP and inhibition of AU-rich element-mediated mRNA decay: implications for novel DMD therapeutics

Abstract: Several therapeutic approaches are currently being developed for Duchenne muscular dystrophy (DMD) including upregulating the levels of endogenous utrophin A in dystrophic fibers. Here, we examined the role of post-transcriptional mechanisms in controlling utrophin A expression in skeletal muscle. We show that activation of p38 leads to an increase in utrophin A independently of a transcriptional induction. Rather, p38 controls the levels of utrophin A mRNA by extending the half-life of transcripts via AU-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 106 publications
(118 reference statements)
0
52
0
Order By: Relevance
“…Anisomycin is known to activate the p38 MAPK pathway, which has been implicated in the regulation of the utrophin gene 19, 21. Two of the strongest utrophin mRNA‐inducing agents identified in the Cmap data, emetine and anisomycin, were p38 MAPK pathway activators ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisomycin is known to activate the p38 MAPK pathway, which has been implicated in the regulation of the utrophin gene 19, 21. Two of the strongest utrophin mRNA‐inducing agents identified in the Cmap data, emetine and anisomycin, were p38 MAPK pathway activators ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Amirouche et al . 21 showed that p38‐mediated phosphorylation of the KH‐type splicing regulatory protein leads to increased stabilization of utrophin A mRNA that in turn caused an increase in utrophin protein (C2C12 cells). Our lab and others have established anisomycin as a potent p38 activator even at low doses 32, 33…”
Section: Discussionmentioning
confidence: 99%
“…The full-length 3′-UTR of the mouse utrophin A mRNA (∼2.1 kb) (39) and the full-length 3′-UTR of the mouse KSRP mRNA (∼1642 kb) were isolated by reverse transcriptase-polymerase chain reaction (RT-PCR) and subcloned downstream of the Firefly luciferase gene driven by the cytomegalovirus (CMV) promoter (pGL4). Cells were cotransfected with 250 ng Firefly luciferase and with 50 ng of Renilla luciferase reporter (phRGtk-luc) to control for transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental protocols were all approved by the University of Ottawa Institutional Animal Care and User Committee. Electrotransfer of pEGP-mmu-miR-206 or pEGP-mmu-miR-Null (Cell Biolabs Inc., San Diego, CA, USA) into tibialis anterior (TA) muscles was performed as described elsewhere (39,40) while the animals were under anesthesia. Ten days after electroporation, the mice were euthanized and muscles were frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation